2020
DOI: 10.1080/02670836.2020.1799136
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on high-temperature mechanical properties of Al–7Si–0.6Mg alloy by wire + arc additive manufacturing

Abstract: The room temperature and high temperature tensile properties of Al–7Si–0.6Mg alloy prepared by wire arc additive manufacturing have been investigated. The results show that the strengthening phase gradually coarsens and the eutectic silicon phase does not grow and agglomerate, meanwhile, the tensile strength and yield strength of the alloy gradually decrease with the increase of temperature. The high-temperature properties of the alloy are better than that of cast alloy. With the increase of temperature, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The Al-7Si-0.6Mg (4220) alloy is suitable for melting-based processing without tendency to crack [ 128 ]. Thus, these alloys are well-suited for WAAM combined with artificial aging [ 129 , 130 ]. Yang et al showed that 4220 in as-deposited state has a relatively poor tensile strength of 130 , but can be raised to 350 in T6 state [ 131 , 132 ].…”
Section: Aluminum Alloys For Waammentioning
confidence: 99%
“…The Al-7Si-0.6Mg (4220) alloy is suitable for melting-based processing without tendency to crack [ 128 ]. Thus, these alloys are well-suited for WAAM combined with artificial aging [ 129 , 130 ]. Yang et al showed that 4220 in as-deposited state has a relatively poor tensile strength of 130 , but can be raised to 350 in T6 state [ 131 , 132 ].…”
Section: Aluminum Alloys For Waammentioning
confidence: 99%
“…Studies have reported that the arc energy influences the microstructure and mechanical properties [18]. With an increase in temperature, the internal porosity and grain size of the aluminium alloy increase, and its tensile and yield strengths gradually decrease [19]. e actively cooled deposition wall has lower surface roughness than the freely cooled deposition wall [20].…”
Section: Introductionmentioning
confidence: 99%